2009
DOI: 10.1016/j.brs.2009.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Role of cortical cell type and morphology in subthreshold and suprathreshold uniform electric field stimulation in vitro

Abstract: Background-The neocortex is the most common target of sub-dural electrotherapy and noninvasive brain stimulation modalities including transcranial magnetic stimulation (TMS) and transcranial current simulation (TCS). Specific neuronal elements targeted by cortical stimulation are considered to underlie therapeutic effects, but the exact cell-type(s) affected by these methods remains poorly understood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

47
589
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 591 publications
(654 citation statements)
references
References 84 publications
47
589
2
1
Order By: Relevance
“…Physiological effects of weak electric fields have been found in in vitro slice preparations at 0.5 mV/mm (14,15), and even at 0.2 mV/mm (16). A minimum threshold of 1 mV/mm has been suggested on the basis of in vivo measurements in rodents (17).…”
Section: Discussionmentioning
confidence: 99%
“…Physiological effects of weak electric fields have been found in in vitro slice preparations at 0.5 mV/mm (14,15), and even at 0.2 mV/mm (16). A minimum threshold of 1 mV/mm has been suggested on the basis of in vivo measurements in rodents (17).…”
Section: Discussionmentioning
confidence: 99%
“…Plasticity effects have been demonstrated only at higher field intensities of~20 V/m (Ranieri et al, 2012;Kronberg et al, 2017). It is possible that network effects amplify electric field effects (Reato et al, 2010) and that larger neurons will be more strongly polarized (Radman et al, 2009) and thus, in vivo effects in human may be stronger than the effects demonstrated for animal in vitro experiments. Future in vivo animal work may shed light on this fundamental question of the required electric field intensities for various physiological effects (e.g., Kar and Krekelberg, 2016).…”
Section: Stimulation Intensitymentioning
confidence: 99%
“…These electrodes are placed over the scalp with the goal of, respectively, increasing and decreasing cortical excitability (Nitsche et al, 2003;Nitsche & Paulus, 2000); although tDCS effects on neuronal processing are in fact more complex (Rahman et al, 2013) and may even invert according to the nature of ongoing activity (Batsikadze, Moliadze, Paulus, Kuo, & Nitsche, 2013). TDCS generates low-intensity electric fields (Datta et al, 2009) in the brain leading to small changes (<1 mV) (Radman, Ramos, Brumberg, & Bikson, 2009) in the membrane potential, thus influencing the frequency of spike timing and modifying net cortical excitability (Purpura & McMurtry, 1965) without triggering action potentials per se (Brunoni et al, 2012;Nitsche et al, 2008). In turn, rTMS causes disruptions in brain activity by delivering strong magnetic pulses to the cortex that pass through the skull and depolarize the underlying neurons of particular areas in the brain Repetitive TMS over the motor cortex facilitates or inhibits brain excitability according to the frequency of stimulation (respectively >1Hz and <1Hz) (Fregni & Pascual-Leone, 2007;George & Aston-Jones, 2010;Hallett, 2007) For cognitive functions, however, there are also other factors that determine rTMS effects, particularly the baseline activity state of the stimulated region ("state-dependency") (Sandrini, Umilta, & Rusconi, 2011;Silvanto, Cattaneo, Battelli, & Pascual-Leone, 2008;van de Ven & Sack, 2013).…”
Section: Introductionmentioning
confidence: 99%